PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN GOJEK DI KOTA BEKASI(STUDI KASUS WARGA HARAPAN JAYA 2) - Chuck Noris Rupelu; Supriyanto, Dody Kurniawan (BORJUIS: JURNAL OF ECONOMY, 2024)
The purpose of this study was to analyze the influence of service quality and price on Gojek customer satisfaction in Bekasi City (case study of Harapan Jaya Residents 2). The research method used is a quantitative method using a questionnaire distributed to 130 respondents. Data analysis was carried out using the t-test and f-test to test the hypothesis. The results of the study indicate that Service Quality and Price have a positive and significant influence on Customer Satisfaction.